USAGE OF INTELLECTUAL TECHNOLOGY FOR AUTOMATIZATION OF TEACHING CONTROL - T.L. Mazurok (Kherson State University, 2013)
The results of the research to identify the features usage of intellectual technologies for to realize of a synergetic model of automatization individual teaching control.